2015
DOI: 10.1007/978-3-319-13117-7_237
|View full text |Cite
|
Sign up to set email alerts
|

Modified Gompertz Equation for Electrotherapy Murine Tumor Growth Kinetics: Predictions and New Hypotheses

Abstract: Background: Electrotherapy effectiveness at different doses has been demonstrated in preclinical and clinical studies; however, several aspects that occur in the tumor growth kinetics before and after treatment have not yet been revealed. Mathematical modeling is a useful instrument that can reveal some of these aspects. The aim of this paper is to describe the complete growth kinetics of unperturbed and perturbed tumors through use of the modified Gompertz equation in order to generate useful insight into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(24 citation statements)
references
References 31 publications
(99 reference statements)
3
21
0
Order By: Relevance
“…Theoretical and experimental results of this study agree and confirm the existence of a threshold of i / i 0 , for which F3II tumor reaches its CR, independently of γ values, as previously reported for Ehrlich and Sa‐37 fibrosarcoma tumors [Ciria et al, ; Cabrales et al, ]. Nevertheless, PR, SD, and DP are obtained for i / i 0 values smaller than this threshold of i / i 0 , depending on the γ value (PR for smaller values of γ , and SD and DP are evidenced for higher values of parameter γ ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Theoretical and experimental results of this study agree and confirm the existence of a threshold of i / i 0 , for which F3II tumor reaches its CR, independently of γ values, as previously reported for Ehrlich and Sa‐37 fibrosarcoma tumors [Ciria et al, ; Cabrales et al, ]. Nevertheless, PR, SD, and DP are obtained for i / i 0 values smaller than this threshold of i / i 0 , depending on the γ value (PR for smaller values of γ , and SD and DP are evidenced for higher values of parameter γ ).…”
Section: Discussionsupporting
confidence: 90%
“…High values of γ mean that DC‐induced net antitumor effect in the tumor happens fast, that is, it has a short‐term effect (inverse of γ ). In this case, the tumor is reorganized and there is re‐growth [Cabrales et al, ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some preclinical studies support the concept of early treatment for cancer because of the exponential tumor growth kinetics presenting as a clinical symptom . Computational modeling of pancreatic cancer therapy showed that early initiation of systemic therapy resulted in a better survival than a delayed therapy .…”
Section: Discussionmentioning
confidence: 99%
“…A significant effort is required to comprehend this problem because the exact shapes of different electrode arrays are usually not given, in spite of the existence of mathematical approaches [11][12][13][14][15][16] and imaging techniques [18,[23][24][25][26][27][28][29][30]. Consequently, there exists a less exhaustive discussion of the comparison between these types of electrode arrays, in spite of the intent of some researchers of evaluating specific electrode configurations [1][2][3][4]6,[17][18][19]31]. Precisely, the aim of this paper is to extend the results of Dev et al [11], Čorović et al [13] and Aguilera et al [14,15] to electrode arrays with different shapes of conic sections (ellipse, parabola and hyperbola).…”
Section: Introductionmentioning
confidence: 99%